LOCAL SHEEP BODY WEIGHT SELECTION RESPONSE ON VARIOUS SELECTION INTENSITY IN PURWAKARTA, WEST JAVA, INDONESIA - Primiani EDIANINGSIH; Dina AMALIA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Research about the local sheep body weight selection response on various selection intensities has been held in Purwakarta, West Java, Indonesia, on November 2017. The aim of the research is to know the heritability and body weight selection response of local sheep as the genetic parameters. The purpose sampling data from 144 sheep (75 male and 69 female derived from six sires), are birth weight (January 2016 until December 2016) and corrected weaning weight on 100 days of age. The variety components and the heritability value were used variance analysis pattern of half-sib correlation. Fixed effect were used sex (male and female) and type of birth (single and twins) the average of birth weight was 2.73 Kg; weaning weight were 6.43 Kg and corrected weaning weight on 100 days of age were 9.32 Kg. Results of analysis data were shown the heritability value of birth weight was 0.32 is high category and the heritability value of corrected weaning weight on 100 days of age was 0.36 also is high category. The highest value of selection response body weight by heritability corrected weaning weight on 100 days (of one sire and eight ewes) with selection intensity 2.03 was 4.22 Kg.